2011
DOI: 10.1021/ja2066913
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Free Sonogashira Cross-Coupling for Functionalization of Alkyne-Encoded Proteins in Aqueous Medium and in Bacterial Cells

Abstract: Bioorthogonal reactions suitable for functionalization of genetically or metabolically encoded alkynes, e.g., copper-catalyzed azide-alkyne cycloaddition reaction (“click chemistry”), have provided chemical tools to study biomolecular dynamics and function in living systems. Despite its prominence in organic synthesis, copper-free Sonogashira cross-coupling reaction suitable for biological applications has not been reported. In this work, we report the discovery of a robust aminopyrimidine-palladium(II) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
260
0
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(280 citation statements)
references
References 47 publications
5
260
0
15
Order By: Relevance
“…Li et al 127 have since shown that by simple methylation of the ligand, the same catalytic system could be used to promote Sonogashira reactions (L2 in Fig. 5a), while the minimal motif guanidine-based ligands (L3 and L4 in Fig.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…Li et al 127 have since shown that by simple methylation of the ligand, the same catalytic system could be used to promote Sonogashira reactions (L2 in Fig. 5a), while the minimal motif guanidine-based ligands (L3 and L4 in Fig.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…Lin developed a palladium-based catalyst for copper free Sonogashira cross-coupling between a peptide/protein carrying a terminal alkyne and a wide range of aryl iodides in aqueous medium [26 ], avoiding the need to use toxic copper(I) [27].…”
Section: Homogenous Pd-mediated Chemistrymentioning
confidence: 99%
“…2 (23-25)) can also be used for bioorthogonal conjugation reactions [43,44,[87][88][89]. Aryl halides can undergo multiple organometalcatalyzed reactions [90,91]. In particular, aryl halides and boronic acids are reactants of the Suzuki reaction [91].…”
Section: Bioorthogonal Labeling Of Proteinsmentioning
confidence: 99%